IDENTIFIKASI MINERAL LOGAM LAYAK TAMBANG BERDASARKAN ANALISA SPECTROMETRI X-RAY FLUORESCENCE DAERAH ABAI BAGIAN UTARA, KECAMATAN SANGIR BATANG HARI, KABUPATEN SOLOK SELATAN, PROVINSI SUMATERA BARAT - Jana Hafiza; Fachrul Rozi Ramadhan (Rang Teknik Journal, 2023)
Solok Selatan is already known as an area that has potential precious metal, Gold. Local mining scale can be found on site certain areas in Abai Region, especially in the North, which was previously believed to exist the presence of these minerals. Based on the consideration of associated mineral associations gold, of course the presence of other precious metals deserves further investigation such as Copper (Cu), Silver (Ag), Lead (Pb), Zinc (Zn) and Titanium (Ti). Exploration activities and geochemical analysis need to be carried out to determine the characteristics of the associated metallic minerals of Gold in Abai Region. A series of explorations carried out with a direct mapping mechanism to determine the topography, morphology, local geology, distribution of lithology and type of gold deposit. The collected samples will be tested in a chemical laboratory to determine gold content, chemical composition, and other metallic minerals. This research is expected to be able to answer the characteristics of the material (mineral) based on the geochemistry of precious metal compounds and can recommend better management in the presence of other precious metals.